Forensic investigation of two Christian and Muslim mass graves skeletal remains in Sorya, Duhok governorate, Iraqi Kurdistan - Amin, Yasin K.; Othman, Goran Qader (Zanco Journal of Medical Sciences (ZJMS), 2020)
Background and objective: This study aimed to investigate two mass graves located in Sorya village, Duhok governorate-Iraqi Kurdistan region. Methods: The investigation included excavation of the graves and identification of the victims. The field study was started after taking testimonies and witnesses for locating the site of graves. Two sites were described (Site 001 and site 002), which were excavated according to the scientific standard procedures. Sex determination, age, and stature estimation were performed on the remained skeletons in the medico-legal institute-Erbil laboratory. Results: Site 001 included 14 bodies, two of them were males and five were females, whereas the others were not identified because of degradations happens to the bones. Site 002 included 25 bodies, which were Christians according to witnesses and supported by evidence. Four victims appeared to be males, 14 were females, and 7 could not be identified. The results of age estimation reported that the number of young bodies in site 001 was five bodies, which represent 35.7% of them all, while 13 out of 25 were young bodies in site 002, which produced 52% of all victims. All the remained bones were recorded in detail for more documentation. Conclusion: This finding described the exhumation and anthropological evaluation of two mass graves in Sorya– Duhok governorate Iraqi Kurdistan region. The majority of the victims were females and contain Christian and Muslims people.